Electrochemical oxidation of lignin for the simultaneous production of bioadhesive precursors and value-added chemicals. (February 2023) - Conde, Julio J.; González-Rodríguez, Sandra; Chen, Xinyi; Lu-Chau, Thelmo A.; Eibes, Gemma; Pizzi, Antonio; Moreira, Maria Teresa
Abstract: Electrochemical oxidation of lignin has been widely regarded as a clean and reliable alternative to obtain value-added products from lignin, such as vanillin or guaiacol. This work aims to go one step beyond the production of low molecular weight molecules and explore the possibility of using lignin residues from electrochemical treatments in the context of biorefinery. To this end, a two-way valorization of lignin by electrochemical oxidation is proposed, in order to obtain a liquid phase enriched in low molecular weight organic oligomers and a solid phase of modified lignin to be used as bioadhesive precursor. Hydroxylation of lignin by electrochemical oxidation using boron-doped diamond (BDD) anodes was observed according to the FTIR and MALDI-TOF results, concluding that an applied current density of 10 mA cm −2 leads to promising modifications for the formulation of bioadhesives. Furthermore, NIPU bioadhesives with electrochemically modified lignin were successfully prepared and tested for use in particleboard panels, showing satisfactory mechanical properties, and thus paving the way for more environmentally friendly lignin modification procedures for the wood industry. Highlights: Organosolv lignin oxidation treatment with BDD electrodes. Double way valorization into low molecular weight oligomers and hydroxylated lignin. Electrochemically modified lignin to be used as bioadhesive precursor.